Final report from the NRC Committee on the Review of the Louisiana Coastal Protection and Restoration (LACPR) Program (National Academies Press, 2009)
"The U.S. Army Corps of Engineers released the Louisiana Coastal Protection and Restoration (LACPR) draft final technical report in March, 2009. In response to federal legislation, the Corps had to analyze hurricane protection, and design and present a full range of measures to protect against a storm equivalent to a category 5 hurricane. The request included measures for flood control, coastal restoration, and hurricane protection, and stipulated close coordination with the State of Louisiana and its appropriate agencies. This is the second and final report from the National Research Council (NRC) Committee on the Review of the Louisiana Coastal Protection and Restoration (LACPR) Program. The committee was charged to review two draft reports from the LACPR team and to assess the hurricane risk reduction framework, alternatives for flood control, storm protection, coastal restoration, and risk analysis. This report presents this committee's review and advice for improvements of the LACPR March 2009 draft final technical report."--Publisher's website